DINAMIKA KEBIJAKAN INFLASI DAN SUKU BUNGA TERHADAP KINERJA PERIKANAN INDONESIA - Ristanti Akseptori; R.A. Norromadani Yuniati; Danis Maulana; Wafi Iqbal Wahyutama (Jurnal Ilmu Manajemen, 2022)
Gross Domestic Product (GDP) as a representation of Indonesia's fisheries performance showed a positive trend from 2011 to 2020. Supportive economic policies are needed to make the fisheries sector the prime mover of national economic development. One of the economic policies is monetary policy. This study aimed to analyze the effect of monetary policy through inflation and interest rates on fishery GDP. The analytical methods used are the Cointegration test and Vector Error Correction Model (VECM). Secondary data were obtained from the Central Statistics Agency, the Indonesian Bank, and the Ministry of Maritime Affairs and Fisheries for the 2011-2020 quarterly. The results showed that inflation and interest rates had no significant effect on Fishery GDP in the short term. Low and stable inflation growth in the long term affects Fishery GDP. Interest Rate did not affect Fishery GDP in the short and long term. This research implies that monetary policy through inflation and interest rates needs to be considered by Bank Indonesia in maintaining macroeconomic stability and financial system stability, as well as encouraging economic growth while considering the dynamics of the global and domestic economy.